Exploring the Learning Psychology Mobilization of Music Majors Through Innovative Teaching Methods Under the Background of New Curriculum Reform - Cai, Haiqin; Liu, Guangliang (Frontiers in Psychology, 2022)
The research expects to explore the psychological mobilization of innovative teaching methods of Music Majors under the new curriculum reform. The relevant theories of college students' innovative teaching methods are analyzed under deep learning together with the innovation and construction of music courses. Thereupon, college students' psychological mobilization is studied. Firstly, the relationship between innovation and entrepreneurship teaching and deep learning is obtained through a literature review. Secondly, the music classroom model is designed based on the deep learning theory, and the four dimensions of the music curriculum are defined to innovate and optimize the music teaching model. Finally, the Questionnaire Survey (QS) is used to analyze the design classroom model. Only 15% of the 180 respondents understand the concept of deep learning, 32% like interactive music learning, and 36% like competitive comparative music classroom learning. And the students who study instrumental music have higher significant differences in learning motivation than those who study vocal music. In addition to classroom learning, 16% of people improve their music skills through music equipment. College students like interactive music classes and competitive comparison classes that can give more play to their subjective initiative. After the new curriculum reform, the music curriculum based on deep learning can stimulate students' interest in learning and participate in the mobilization of students' learning psychology. Therefore, in the future of music education and teaching, there is a need to pay more attention to students' psychological status. The research results can provide references and practical significance for the innovative teaching activities of music classrooms after the new curriculum reform.